Evaluating the Balance between Intrinsic and Extrinsic Motivation in Aspiring Teachers: A Case Study at a Public University - Sheeza Asif; Deng Xiaoqing; Shaharia Sharmin Shrabonty; Akash Mahamud (Al-Qanṭara, 2024)
This study aims to examine the intricate balance between intrinsic and extrinsic motivation among prospective teachers enrolled in the Bachelor of Education (B.Ed.) program at Bahauddin Zakariya University, Multan, Pakistan. Motivation, a critical determinant in the educational and professional trajectories of future educators, was analyzed to assess how internal and external factors influence teaching preparedness. Using a descriptive research design, a sample of 74 students was surveyed with a 36-item Likert scale that evenly distributed items between intrinsic (internal satisfaction, intellectual curiosity) and extrinsic (external rewards, social validation) motivators. The results revealed a slight predominance of extrinsic motivation (mean score = 3.93) over intrinsic motivation (mean score = 3.89), suggesting that external factors such as grades, teacher validation, and task ease were marginally more influential than internal factors like personal challenge and problem-solving. Despite this, intrinsic motivation remained strong, particularly in areas related to intellectual engagement and independent problem-solving. A notable finding was the significant negative correlation between intrinsic and extrinsic motivation, indicating that an increase in reliance on external motivators tends to diminish internal motivation, and vice versa. These findings offer significant insights for teacher education programs, highlighting the need for a balanced motivational strategy that integrates both intrinsic and extrinsic elements. Future educators should be encouraged to cultivate a passion for teaching through personal satisfaction while also being guided by external milestones, such as academic performance and career prospects. The study recommends further exploration into how these motivational orientations evolve over time, and their impact on long-term teaching effectiveness and job satisfaction. By aligning curricula with both intrinsic and extrinsic motivators, educational institutions can better prepare future teachers for the multifaceted demands of the profession.